Pollen counts in sediment core SF-07 obtained along the coastal plain of Babitonga Bay-Santa Catarina-Brazil - Cohen, Marcelo Cancela Lisboa; Fontes, Neuza; Rodrigues, Érika do Socorro Ferreira; Pessenda, Luiz C R; França, Marlon; Garret, Ed; Ryu, Junghyung (In: Cohen, MCL et al. (2025): Topographic, vegetation, radiocarbon and stratigraphic data from Babitonga Bay-Santa Catarina-Brazil [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.985002, 2025)
Fieldwork was conducted in August 2017 to sample sediment cores. The sediment cores were subsampled (1 cm³) at 5 cm intervals, resulting in a total of 125 samples that were processed using standard pollen analytical techniques, including acetolysis (Faegri and Iversen, 1989).
Keywords: isotopes; mangrove; radiocarbon age; South Brazil